2022
DOI: 10.1007/s00464-022-09280-0
|View full text |Cite
|
Sign up to set email alerts
|

Linked color imaging improves identification of early gastric cancer lesions by expert and non-expert endoscopists

Abstract: Background and aims Early gastric cancer (EGC) lesions are often subtle and endoscopically poorly visible. The aim of this study is to evaluate the additive effect of linked color imaging (LCI) next to white-light endoscopy (WLE) for identification of EGC, when assessed by expert and non-expert endoscopists. Methods Forty EGC cases were visualized in corresponding WLE and LCI images. Endoscopists evaluated the cases in 3 assessment phases: Phase 1: WLE ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The proportion of overlooked neoplasms was lower in the LCI group (0.67%) than in the WLI group (3.5%); risk ratio, 0.19 [CI 0.07–0.50] Hiraoka et al [ 65 ] 2021 Retrospective/SC 40 Images of EGCs and surrounding mucosa The mean visibility scores for LCI with C2 enhancement were significantly higher than those with C1 enhancement. LCI with C2 enhancement tended to produce a color difference between the malignant lesions and the surrounding mucosa Fockens et al [ 66 ] 2022 Retrospective/MC 40 EGC lesions Images of EGCs Experts reached higher consensus on discrimination between neoplasia and inflammation when using LCI. Non-experts placed the biopsy mark more accurately with LCI (82.3% vs. 87.2%, P < 0.001).…”
Section: Lci For Screening Of Egcmentioning
confidence: 99%
“…The proportion of overlooked neoplasms was lower in the LCI group (0.67%) than in the WLI group (3.5%); risk ratio, 0.19 [CI 0.07–0.50] Hiraoka et al [ 65 ] 2021 Retrospective/SC 40 Images of EGCs and surrounding mucosa The mean visibility scores for LCI with C2 enhancement were significantly higher than those with C1 enhancement. LCI with C2 enhancement tended to produce a color difference between the malignant lesions and the surrounding mucosa Fockens et al [ 66 ] 2022 Retrospective/MC 40 EGC lesions Images of EGCs Experts reached higher consensus on discrimination between neoplasia and inflammation when using LCI. Non-experts placed the biopsy mark more accurately with LCI (82.3% vs. 87.2%, P < 0.001).…”
Section: Lci For Screening Of Egcmentioning
confidence: 99%
“…Recently, Fockens et al . reported that LCI enabled recognition of lesions to be biopsied more accurately than did WLI for nonexperts, but there was no comparison with experts 22 . Yoshifuku et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fockens et al reported that LCI enabled recognition of lesions to be biopsied more accurately than did WLI for nonexperts, but there was no comparison with experts. 22 Yoshifuku et al also reported that LCI significantly improved the visibility of gastric cancer compared with blue laser imaging regardless of the doctor's experience. 23 Our data showed that LCI was advantageous for nonexperts, especially novices, in detecting epithelial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The first test set was benchmarked by 52 general endoscopists originating from 3 countries to provide a reference for CADe performance. A previously designed web‐based module (Meducati AB, Göteborg, Sweden) was used and adjusted for this specific study 15,16 . For each endoscopic image, the endoscopists indicated if they detected neoplasia and, where applicable, placed a biopsy mark on the most abnormal part of the lesion.…”
Section: Methodsmentioning
confidence: 99%
“…A previously designed web‐based module (Meducati AB, Göteborg, Sweden) was used and adjusted for this specific study. 15 , 16 For each endoscopic image, the endoscopists indicated if they detected neoplasia and, where applicable, placed a biopsy mark on the most abnormal part of the lesion. This mark represents the location where they would have taken a targeted biopsy during real‐time endoscopic examination.…”
Section: Methodsmentioning
confidence: 99%